Changes in Transcriptome of Yersinia pseudotuberculosis IP32953 Grown at 3 and 28°C Detected by RNA Sequencing Shed Light on Cold Adaptation - Virtanen, Jussa-Pekka; Keto-Timonen, Riikka; Jaakkola, Kaisa; Salin, Noora; Korkeala, Hannu (Frontiers in Cellular and Infection Microbiology, 2018)
Yersinia pseudotuberculosis is a bacterium that not only survives, but also thrives, proliferates, and remains infective at cold-storage temperatures, making it an adept foodborne pathogen. We analyzed the differences in gene expression between Y. pseudotuberculosis IP32953 grown at 3°C and 28°C to investigate which genes were significantly more expressed at low temperature at different phases of growth. We isolated and sequenced the RNA from six distinct corresponding growth points at both temperatures to also outline the expression patterns of the differentially expressed genes. Genes involved in motility, chemotaxis, phosphotransferase systems (PTS) and ATP-binding cassette (ABC) transporters of different nutrients such as fructose and mannose showed higher levels of transcripts at 3°C. At the beginning of growth, especially genes involved in securing nutrients, glycolysis, transcription, and translation were upregulated at 3°C. To thrive as well as it does at low temperature, Y. pseudotuberculosis seems to require certain cold shock proteins, especially those encoded by yptb3585, yptb3586, yptb2414, yptb2950, and yptb1423, and transcription factors, like Rho, IF-1, and RbfA, to maintain its protein synthesis. We also found that genes encoding RNA-helicases CsdA (yptb0468), RhlE (yptb1214), and DbpA (yptb1652), which unwind frozen secondary structures of nucleic acids with cold shock proteins, were significantly more expressed at 3°C, indicating that these RNA-helicases are important or even necessary during cold. Genes involved in excreting poisonous spermidine and acquiring compatible solute glycine betaine, by either uptake or biosynthesis, showed higher levels of transcripts at low temperatures. This is the first finding of a strong connection between the aforementioned genes and the cold adaptation of Y. pseudotuberculosis. Understanding the mechanisms behind the cold adaptation of Y. pseudotuberculosis is crucial for controlling its growth during cold storage of food, and will also shed light on microbial cold adaptation in general.